Reporting a Rare Case of an Ovarian Dermoid Cyst Containing Intestine - A Mansouri; M Sadeghi; F Kianifar; K Momeni; M Mahdavi Zafarghandi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Dermoid cysts or mature cystic teratoma are one of the most common benign ovarian tumors. In this study, a case of rare ovarian dermoid cyst containing hair, teeth, bone and intestine is reported. Case Report: The patient is a 36-year-old woman who referred with abdominal pain, nausea and change in menstruation since 2 months ago. The pain was not related to menstruation and there was no tenderness in the abdomen. Diagnosis of the mass was performed with ultrasound and MRI, and a cystic mass was detected in the right and left ovary. The patient underwent laparoscopic surgery. During the operation, the right ovary and the left ovarian cyst were removed completely and without damage. The dermoid cyst of the right ovary contained hair, teeth, bones and nails. The patient was discharged 1 day after the operation, and no complications from the surgery were reported in the follow-up. In the pathological examinations, intestinal tissue was seen in the cyst, which is important, so this case was reported. Conclusion: According to the results of this reported case, intestinal tissue may be present in dermoid cyst. Complete resection is recommended in these patients.